Turn taking and ‘wait time’ in classroom interactions - Ingram, J; Elliott, V (Elsevier, 2014)
In this paper we examine classroom interactions using a conversation analytic approach to explore the relationship between turn taking and silences in classroom interaction. Seventeen mathematics lessons with pupils aged between 12 and 14 years were analysed in terms of the structure of turn taking and the length and nature of pauses that occurred during whole class interactions. We show that the turn taking structure of classroom interactions remains consistent with that described in the conversation analytic literature. In classroom interactions where different turn taking structures apply, silences have a different influence on student and teacher behaviour. We then demonstrate that the pedagogical construct of wait time is structurally built into classrooms with a formal turn taking structure and that this structure explains many of the previous research findings relating to the length of wait time. These findings have implications for pedagogic policies and recommendations relating to classroom interactions.